Security and conflict in East Asia - Tan, Andrew T. H. (Andrew Tian Huat) (Abingdon, Oxon : Routledge, 2015)
'This volume has been prompted by the high tensions on the Korean peninsula and between the People's Republic of China and Japan in recent years. Examining China's military modernization and relationship with the USA, the regional arms race and the security challenges facing Japan and the Korean peninsula, this title aims to assist in a better understanding of the issues in the region, to suggest possible solutions, and to draw attention to the need for diplomacy, confidence-building measures, crisis management mechanisms and other measures to prevent conflict'--
The prospects for conflict in East Asia / Andrew T.H. Tan -- The international relations of East Asia from a historical perspective / Andrea Benvenuti -- Arms racing in East Asia / Andrew T.H. Tan -- China's naval modernization and its impact on Asian security / Nan Li -- China's East Asia policy since 2009 / Nicholas Khoo -- US-China strategic rivalry in East Asia: trouble ahead? / Robert Sutter -- The pivot and Peking: the US response to China East Asia / Richard A. Bitzinger -- Stuck over the barren rocks: the Diaoyu/Senkaku Islands dispute and Sino-Japanese relations / Jingdong Yuan -- China's fluid assertiveness in the South China Sea dispute / Mingjiang Li and Loh Ming Hui Dylan -- China and the Strait of Malacca / Justin V. Hastings -- China's strategy towards Taiwan / Sheryn Lee -- Taiwan's defence options / Benjamin Schreer -- Japan's decline and the consequences for East Asian conflict and cooperation / Christopher W. Hughes -- Nationalism and revisionism: hijacking Japan's security and defence policy agenda? / Axel Berkofsky -- Japan's defence: challenges and future direction / Brad Williams -- Prospects of conflict in Korea: the threat of North Korea's continuing WMD programme and unreformed economy / Nolan Theisen -- The paradoxes of vulnerability: managing North Korea's threat to regional security / Andrew O'Neil -- Park Geun-hye, foreign policy innovation and risk on the Korean peninsula / John Swenson-Wright -- North Korea endgame / Terence Roehrig -- China's future role in East Asia / Richard Weixing Hu -- The future role of the USA in East Asia / Paul J. Smith -- Preventing the next war in East Asia / Andrew T.H. Tan.
Includes bibliographical references and index.
Keywords: National security -- East Asia; National security -- East Asia